2022
DOI: 10.1556/2055.2022.00024
|View full text |Cite
|
Sign up to set email alerts
|

Content biases in three phases of cultural transmission: A review

Abstract: Cultural evolution theory proposes that information transmitted through social learning is not transmitted indiscriminately but is instead biased by heuristics and mechanisms which increase the likelihood that individuals will copy particular cultural traits based on their inherent properties (content biases) and copy the cultural traits of particular models, or under particular circumstances (context biases). Recent research suggests that content biases are as important, or more important, than context biases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 230 publications
(285 reference statements)
0
10
0
Order By: Relevance
“…schema) that they already know [ 62 , 63 ]. Previous experiments have shown that cognitive biases shape folklore in certain directions [ 62 64 ]. Such cognitive or behavioural processes may shape folklore incorporating trickster animals whose corresponding real animals were familiar to locals.…”
Section: Discussionmentioning
confidence: 99%
“…schema) that they already know [ 62 , 63 ]. Previous experiments have shown that cognitive biases shape folklore in certain directions [ 62 64 ]. Such cognitive or behavioural processes may shape folklore incorporating trickster animals whose corresponding real animals were familiar to locals.…”
Section: Discussionmentioning
confidence: 99%
“…Work in cultural evolution has suggested a content bias for general threat‐related information in social transmission. This bias increases the likelihood that information about threats will be attended to, believed, encoded in memory, and passed on to others, increasing their prevalence in culture (Stubbersfield, 2022). This has been demonstrated experimentally using micro‐society designs (Blaine & Boyer, 2018; Moussaïd et al, 2015; Stubbersfield et al, 2015), and has been found to be relevant to the propagation of rumours (Knapp, 1944), front page news (Davis & McLeod, 2003), ‘fake news’ (Acerbi, 2019), urban legends (Fessler et al, 2014; Stubbersfield et al, 2017), and international supernatural beliefs (Fessler et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the content of transmission, Ishiyama et al (2012) demonstrated that people, in general, can show a more positive attitude toward the medical setting than the nonmedical setting. One of the main reasons for this attitude can be explained by a possible threat bias ( Mesoudi and Whiten, 2008 ; Stubbersfield, 2022 )—that is, people may consider diseases the greatest threat to their lives. Our analysis indicates that while people are aware of basic genetic terms, social benefits, and concerns, they may not be familiar with some of the specific technical terms and rules of GR.…”
Section: Discussionmentioning
confidence: 99%
“…However, knowledge and information are not passed linearly, since individuals make selective use of information—a situation called content bias ( Boyd and Richerson, 1985 ; Mesoudi and Whiten, 2008 ). Several content biases are classified in cultural transmission as being related to the kind of information that is copied more easily–namely, i) payoff bias (i.e., a trait with a higher payoff being copied), ii) emotion bias (i.e., a trait provoking disgust being more likely to be copied than other traits), iii) threat bias (i.e., words related to potential threats and survival potentially being recalled better than other words), and iv) social bias (i.e., putting greater emphasis on a trait’s moral aspects than on its efficacy) ( Mesoudi and Whiten, 2008 ; Stubbersfield, 2022 ). An example of biased transmission may be individuals exhibiting a more positive reaction toward GR in medical contexts than in other contexts.…”
Section: Rationalementioning
confidence: 99%